2017
DOI: 10.31092/jia.v1i1.69
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Sharia and Conventional Mutual Funds During 2008 and 2013 Crisis Periods

Abstract: This research has a purpose to analyze the performance of sharia and conventional mutual funds, particularly equity mutual funds in Indonesia during 2008 and 2013 crisis periods. Within 2008 crisis period, the data set comprises of 51 equity mutual funds in which 4 were sharia mutual funds while 47 others were conventional mutual funds. Moreover, within 2013 crisis period, the data set comprises of 110 equity mutual funds in which 12 were sharia mutual funds while 98 others were conventional mutual funds. To m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Relatively, the actively managed Tata Ethical Fund performed better in the first sub-period, by not generating a negative alpha, unlike the passive NSE Sharīʿah 500 index. Jensen's Alpha in the previous studies (Yudanto, 2017;Karim and Panetta, 2014;Setiawan and Oktariza, 2013;Munusamy and Natarajan, 2011;Singh and Das, 2013), are either not estimated through regressions like in this paper or are estimated on monthly frequencies (Elfakhani et al, 2005), and therefore, cannot be compared with the results in this paper. Jensen's Alpha of NSE Sharīʿah 50 is the weakest of the SCEIs.…”
Section: Investment Horizon and Market Volatilitymentioning
confidence: 80%
See 1 more Smart Citation
“…Relatively, the actively managed Tata Ethical Fund performed better in the first sub-period, by not generating a negative alpha, unlike the passive NSE Sharīʿah 500 index. Jensen's Alpha in the previous studies (Yudanto, 2017;Karim and Panetta, 2014;Setiawan and Oktariza, 2013;Munusamy and Natarajan, 2011;Singh and Das, 2013), are either not estimated through regressions like in this paper or are estimated on monthly frequencies (Elfakhani et al, 2005), and therefore, cannot be compared with the results in this paper. Jensen's Alpha of NSE Sharīʿah 50 is the weakest of the SCEIs.…”
Section: Investment Horizon and Market Volatilitymentioning
confidence: 80%
“…The evidence so far seems to be conflicting and inconclusive. Elfakhani et al (2005), Rizvi and Arshad (2014), Setiawan and Oktariza (2013), Yudanto (2017) and Boo et al (2017) show that there is no significant difference in the return performance between Islamic and non-Islamic funds. However, Ismail and Shakrani (2003) and Karim and Panetta (2014) show that Islamic Unit Trusts and Indices, respectively, perform better than their non-Islamic counterparts.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Similarly, research (Syafrida et al, 2015) which states there is no significant difference between the performance of sharia and conventional instruments. The research was also carried out by (Yudanto, 2016) which revealed that there was no difference in the performance of sharia and conventional mutual funds in 2008. Research was also conducted (Hilman, 2017) which said there were no significant differences between sharia and non-sharia mutual funds.…”
Section: Research Findings and Discussionmentioning
confidence: 99%
“…In 2010, there were 48 sharia mutual funds are operating, while conventional mutual funds are 564. In the three-year intervals, which is 2013, the increase in sharia mutual funds did not occur significantly, where the number of sharia mutual funds in 2013 only reached 7.90% of the total number of mutual funds operating both sharia mutual funds as well as conventional (Yudanto, 2017). Meanwhile, in the same year there were 92.15% conventional mutual funds.…”
Section: Development Of Islamic Mutual Funds In Indonesiamentioning
confidence: 91%